Core Competencies for Shared Decision Making Training Programs: Insights From an International, Interdisciplinary Working Group1. Issue 4 (September 2013) - Légaré, France; Moumjid‐Ferdjaoui, Nora; Drolet, Renée; Stacey, Dawn; Härter, Martin; Bastian, Hilda; Beaulieu, Marie‐Dominique; Borduas, Francine; Charles, Cathy; Coulter, Angela; Desroches, Sophie; Friedrich, Gwendolyn; et al.
Abstract Shared decision making is now making inroads in health care professionals' continuing education curriculum, but there is no consensus on what core competencies are required by clinicians for effectively involving patients in health‐related decisions. Ready‐made programs for training clinicians in shared decision making are in high demand, but existing programs vary widely in their theoretical foundations, length, and content. An international, interdisciplinary group of 25 individuals met in 2012 to discuss theoretical approaches to making health‐related decisions, compare notes on existing programs, take stock of stakeholders concerns, and deliberate on core competencies. This article summarizes the results of those discussions. Some participants believed that existing models already provide a sufficient conceptual basis for developing and implementing shared decision making competency‐based training programs on a wide scale. Others argued that this would be premature as there is still no consensus on the definition of shared decision making or sufficient evidence to recommend specific competencies for implementing shared decision making. However, all participants agreed that there were 2 broad types of competencies that clinicians need for implementing shared decision making: relational competencies and risk communication competencies. Further multidisciplinary research could broaden and deepen our understanding of core competencies for shared decision making training.